2020
DOI: 10.1021/jacs.9b13391
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl Benzoxazines and Dihydroquinazolines as Cysteine Targeting Covalent Warheads and Their Application in Identification of Selective Irreversible Kinase Inhibitors

Abstract: With a resurgence in interest in covalent drugs, there is need to identify new moieties capable of cysteine bond formation that are differentiated from commonly employed systems such as acrylamide. Herein, we report on the discovery of new alkynyl benzoxazine and dihydroquinazoline moieties capable of covalent reaction with cysteine. Their utility as alternative electrophilic warheads for chemical biological probes and drug molecules is demonstrated through site-selective protein modification and incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 52 publications
1
68
0
Order By: Relevance
“…The acquirement of high selectivity for a covalent inhibitor to reduce off-target reactions requires that the intrinsic reactivity of the electrophilic warhead on the inhibitor should be low. The half-life of the electrophile to react with glutathione (GSH t 1/2 ) is a useful assay for measuring the intrinsic reactivity of cysteine-targeted warheads, and for providing information about the electrophilicity and liability toward forming reactive intermediates 24 , 27 , 28 . To determine the rates of reaction with GSH, a range of concentrations of myricetin, baicalein or N-phenylacrylamide (a positive control) were incubated with GSH, and the remaining compounds at varying time was determined by liquid chromatography-tandem mass spectrometry (LC-MS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquirement of high selectivity for a covalent inhibitor to reduce off-target reactions requires that the intrinsic reactivity of the electrophilic warhead on the inhibitor should be low. The half-life of the electrophile to react with glutathione (GSH t 1/2 ) is a useful assay for measuring the intrinsic reactivity of cysteine-targeted warheads, and for providing information about the electrophilicity and liability toward forming reactive intermediates 24 , 27 , 28 . To determine the rates of reaction with GSH, a range of concentrations of myricetin, baicalein or N-phenylacrylamide (a positive control) were incubated with GSH, and the remaining compounds at varying time was determined by liquid chromatography-tandem mass spectrometry (LC-MS).…”
Section: Resultsmentioning
confidence: 99%
“…Targeting the nucleophile of a specific cysteine or serine residue of enzymes with electrophilic reactive groups, the so-called warheads, is the predominant strategy in targeted covalent inhibitor development 20 22 . For example, boceprevir and telaprevir, two drugs approved by the FDA for the treatment of hepatitis C virus (HCV) infection, both utilize a warhead of ketoamide to covalently react with the catalytic serine of the HCV NS3 protease 23 , 24 . Noteworthy, there has been a very high interest in characterization of alternative warheads to meet a large variety of requirements in medicinal chemistry and chemical biology, though cysteine/serine-targeted Michael acceptors such as acrylamides and other α,β-unsaturated carbonyls are the predominant warheads in the realm of current covalent drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Novolactone which can covalently react with Glu-444 of hHsp70 also shows a promising inhibition effect on function of hHsp70 (27). Development of covalent inhibitors targeting cysteine residues in kinases has been a focus for cancer therapy for a long time, as the irreversibility of covalent binding prolongs pharmacodynamics and there is potential for flexible rational design to give high potency and high specificity (44)(45)(46). In addition to acrylamide inhibitors, alkyne inhibitors targeting thiols in proteins also show promise for drug development (44,47).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that nitrogen-based nucleophiles (6), such as aliphatic amines [25][26][27], anilines [28][29][30][31], or hydrazines [32,33], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [34][35][36]. Employing strategically placed second nucleophilic functionality (carbon or heteroatom-based), the resulting amidinium species (7) can be transformed into a variety of heterocyclic compounds, such as benzoxazoles (8) [23,28] or benzimidazoles (9) [28], perimidines (10) [29], 6,7-dihydro-1H-cyclopenta[gh]perimidines (11) [31], 1,3,4-oxa-di-azoles (12) [32,33], imidazolines (13) [25], 3,4-dihydro-iso-quinolines (14) [27], imidazo [1,5-a]pyridines (15) [26], and [1,2,4]triazolo [4,3-a] It occurred to us that a similar strategy can be applied for the straightforward preparation of 3,4-dihydroquinazolines as well. In reaction with bis-nucleophilic 2-(aminomethyl) anilines (1), the phosphorylated nitronate species 5 would, after elimination of orthophosphoric acid entity, afford an amidinium intermediate 7 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Since 2-(aminomethyl)aniline ( 1 ) can be viewed as a bis-nucleophilic synthon, all these annulations are designed as double-fold attacks at reagents that can serve as a 1,1-bis-electrophilic synthetic equivalent ( Scheme 1 ). Typically, carboxylic acids [ 9 , 10 , 11 , 12 , 13 ], nitriles [ 14 ], or other related carbonyl derivatives [ 15 , 16 , 17 ] ( 2 ) are employed ( Scheme 1 ). Oxidative protocols utilizing aldehydes as alkylating reagents were also reported [ 18 , 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%